Ginástica e inclusão nas produções acadêmicas de 2012 a 2021 - SANTOS, Alexandre da Silva (2023)
Given the importance of gymnastics as a manifestation of Corpora Culture and the recognition of the importance of inclusion in Physical Education classes, the present study focuses on the relationship between gymnastics and the process of inclusion of people with disabilities, questioning: the possibilities of gymnastics in the process of including people with disabilities in Physical Education classes? Thus, its main objective is to investigate the possibilities of gymnastics for the inclusion of people with disabilities, in academic productions from 2012 to 2021. For this, a systematic review of the works published between the years 2011 to 2021, present in the database Google Scholar, dealt with the practice of including people with disabilities through gymnastics. Thirteen (13) works were found, 7 (seven) were articles presented at conferences, 3 (three) were articles published in journals and 3 (three) were course conclusion works. The investigated gym production revealed that the relationship between gymnastics and inclusion still needs further studies. On the other hand, the analyzed studies pointed out that gymnastics approached from the perspective of inclusion promotes the development of motor aspects; improves the balance of its practitioners, which can reduce the risk of falling; promotes interaction and the development of affective-social relationships; living with differences; the improvement of self-esteem, self-confidence, and acceptance, especially when well planned and in a playful way, always seeking to encourage creativity and interaction between practitioners.